Analysis of the Proximate Composition of Domesticated Stock of Pangas (Pangasianodon hypophthalmus) in Laboratory Condition - Begum, M; Akter, T; Minar, MH (Journal of Environmental Science and Natural Resources, 2012)
A study was undertaken to determine the proximate composition of aquarium reared pangus (Pangasianodon hypophthalmus) fish. Fresh aquarium pangas fish were used during the whole experiment and the fishes were under identical rearing conditions from fingerling till adult. The proximate biochemical composition of domesticated stock of raw pangas muscles were determined through determination of moisture, Protein, Fat and Ash of the edible portion. And the results indicates the moisture, protein, fat and ash percentage (%) were 78.29 ±0.22, 12.78 ±0.16, 16.55 ± 1.52 and 1.78 ±0.19, respectively. Therefore, this fish can play a significant role to fulfill the nutrient demand of the people in Bangladesh. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11555 Environ. Sci. & Natural Resources, 5(1): 69-74, 2012